GSDKM : uma estrutura de apoio ao desenvolvimento global de software por meio de práticas de gestão do conhecimento - Beninca, Romulo de Aguiar (2015)
Currently, several organizations producing software adopt the Distributed Software Development (DSD), in order to achieve competitive advantages over competitors. But to enjoy the DSD beneficial, it is necessary to deal with many challenges imposed on it, which are even more apparent when the distribution occurs globally (GSD - Global Software Development). Several of these challenges are related to the lack of use of Knowledge Management (KM) in GSD. Thus, the use of KM is directly related to productivity and may even determine the success or failure of globally distributed projects. Although the importance of using KM in GSD is recognized, they have not been identified in the literature, models that offer adequate support for using KM specifically in globally distributed software development environments. Thus, the purpose of this dissertation is to present a model that provides support to the GSD with the use of KM through Knowledge Management Practices (KMP), named GSDKM. So, Development Process; Development artifacts; Human Resources involving roles for KM and also for software development; KM artifacts; KMPs, KM Strategy; Tools, Repository including a knowledge base, integrate this structure. To illustrate an example of use of GSDKM structure was considered a scenario, fictitious, to develop an application GSD. Aiming at to assess the GSDKM structure was also conducted a feasibility study. The results of this feasibility study indicated that; (I) the constituents of the structure are necessary and important to support GSD with KM; (II) it is possible to customize the frame to suit applications of different complexities; (III) the set KM roles are sufficient. Still, as major contributions we have: (a) identification of the challenges present in GSD due to lack of use of KM; (b) identification of KM practices that can be used to mitigate these challenges; and (c) the identification of elements for the elaboration of a structure that supports GSD through the use of KMP's.